Biodegradation of gamma-sterilised biomedical polyolefins under composting and fungal culture environments - Alariqi, Sameh A. S.; Kumar, A. P.; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2006)
Polyolefin-based commodities are widely used as biomedical devices and food packaging after gamma-sterilisation. The aim of the present work was to study the effect of gamma-sterilisation on the biodegradation of polyolefins. Films of isotactic polypropylene, high-density polyethylene and ethylene-propylene (EP) copolymers were sterilised under gamma-radiation with doses of 10 and 25 kGy. Neat and sterilised samples were incubated in compost and fungal culture environments. The changes in functional groups, surface morphology and chain scission in polymer chains were characterized by FTIR spectroscopy, SEM and viscometric measurements, respectively. A gradual decrease in intrinsic viscosity [eta] and increase in carbonyl and hydroxyl regions in FTIR spectra were found for the gamma-sterilised samples as a function of increasing dose. Polypropylene was found to be more susceptible to both radio-oxidation and biodegradation. It was observed that in case of ethylene-propylene copolymers, extent of gamma-sterilisation and/or biodegradation depends on the composition and distribution of comonomers. Important surface erosion was detected by SEM, for higher sterilisation doses, after composting. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; chain scission; Composting and fungal culture; gamma-sterilisation; Polyolefins

Stabilization of gamma-sterilized biomedical polyolefins by synergistic mixtures of oligomeric stabilizers - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Tevtia, Amit K.; Singh, R. P. (Polymer Degradation and Stability, 2006)
The stabilization of polyolefins against gamma-sterilization has been studied with single or binary additive system. The present attempt is to utilize synergistic mixtures of stabilizers which are approved for food contact applications. Ethylene-propylene (EP) copolymer has been melt-mixed with hindered amine stabilizers (HAS), phenolic antioxidants and organo-phosphites (hydroperoxide decomposer). Samples were sterilized with different doses of gamma-radiation. Stabilization was characterized in terms of changes in the functional groups (oxidation products), tensile properties, yellowing and surface morphology by FTIR spectroscopy, Instron, colorimetry (reflectance) and scanning electron microscopy (SEM), respectively. Results were discussed by comparing the stabilizing efficiency of mixtures with and without phenol system. Among phenol containing systems, where we mostly observe discoloration due to the oxidation of hindered phenol and the combination of secondary HAS, tertiary HAS, organo-phosphite and hindered phenol exhibited improved stabilization efficiency than single or binary additive systems. The mixture of secondary HAS and tertiary HAS, has shown antagonistic effect of stabilization whereas their combination with organo-phosphite has exhibited synergistic effect of stabilization even at higher doses of gamma-sterilization. The effects have been explained through the interaction between the stabilizers. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Antioxidants; discoloration; ethylene-propylene copolymer; gamma-sterilization; stabilization; tensile properties

Stabilization of gamma-sterilized biomedical polyolefins by synergistic mixtures of oligomeric stabilizers. part II. polypropylene matrix - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2007)
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Effect of gamma-dose rate on crystallinity and morphological changes of gamma-sterilized biomedical polypropylene - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2009)
The present work is aimed to study the changes in crystallinity and morphology of biomedical polyolefins after gamma-sterilization. The isotactic polypropylene (iPP) films were sterilized by gamma-radiation and the changes were characterized by differential scanning calorimetry (DSC), wide angle X-ray diffraction (WAXD) and atomic force microscopy (AFM) techniques. The effect of dose rate on crystallinity changes also was focused. It was found that crystallinity and morphology significantly changed with gamma-irradiation. There was an increase in crystallinity Lip to 10 kGy accompanied with decrease in viscosity and mechanical properties. The changes in crystallinity mainly depend on gamma-irradiation dose and dose rate. The rise in crystallinity was attributed to chain scission and forming new perfect lamellae. However, the reduction was accompanied by occurrence of gamma- and beta-phases and crosslinking. Possible explanations for transitions in phases are also discussed based on our results. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Crystallinity; Dose rate; Gamma radiation; mechanical properties; Morphology; polypropylene

Gamma-initiated oxidation of isotactic polypropylene: effect of gamma-dose rate on durability - Alariqi, Sameh A. S.; Singh, R. P.; Rao, B. S. M. (Arabian Journal for Science and Engineering, 2011)
The effect of gamma-irradiation dose rate on the chemical, molecular, and mechanical properties of isotactic polypropylene (iPP) films was investigated using three different Co-60 sources with dose rates of 600, 660, and 780 Gy h(-1). Fourier transform infrared spectroscopy coupled with chemical derivatization with NO and SF4, and measurements of the elongation at break, toughness, and molecular weight were used to describe the effects of gamma-dose rate on iPP. It was found that the formation of oxidation products depended significantly on the dose rate. However, the kinetic accumulation of ketones were more sensitive to the dose rate of gamma source. Degradation induced by gamma-radiation depends on the dose rate-the degradation of mechanical properties was more significant at a low dose rate than at a high dose rate. It was found that the lower the dose rate, the higher the degree of oxidation in terms of the formation of gamma-products. The mechanism of gamma-degradation is discussed based on the correlation between the changes in chemical and physical properties upon exposure to gamma-radiation.
Keywords: Chemical and physical properties; Dose rate; gamma-irradiation; polypropylene